The Concept of Islamic Education from the Perspective of K.H. Hasyim Asy'ari - Livia, Diana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to discuss the concept of Islamic education from the perspective of K.H. Hasyim Asy'ari. His thoughts are rooted in classical Islamic treasures, especially the Shafi'iyyah and Sufism traditions, but remain relevant to the modern context. The focus of this study includes the objectives, curriculum, methods, evaluation, and contributions of his education to society. This study uses a qualitative approach with a library research method, namely reviewing the works of K.H. Hasyim Asy'ari such as Adab al-'Alim wa al-Muta'allim and relevant secondary literature, then analyzed descriptively and analytically. The results of the study indicate that the goal of education according to K.H. Hasyim Asy'ari is to form a perfect human being who is knowledgeable, moral, faithful, and beneficial to the community. The educational curriculum he initiated emphasizes the teaching of turats books and adab as the core, but remains open to general knowledge that supports the religious mission. The educational methods applied include sorogan, bandongan, halaqah, uswah hasanah, and riyadhah, which integrate cognitive, affective, and spiritual aspects. According to him, educational evaluation emphasizes the blessings of knowledge, morals, and practice, not merely academic achievement.